2000
DOI: 10.1074/jbc.c000314200
|View full text |Cite
|
Sign up to set email alerts
|

Arrestin Binding to the G Protein-coupled N-Formyl Peptide Receptor Is Regulated by the Conserved “DRY” Sequence

Abstract: Following activation by ligand, the N-formyl peptide receptor (FPR) undergoes processing events initiated by phosphorylation that lead to receptor desensitization and internalization. Our previous results have shown that FPR internalization can occur in the absence of receptor desensitization, suggesting that FPR desensitization and internalization are controlled by distinct mechanisms. More recently, we have provided evidence that internalization of the FPR occurs via a mechanism that is independent of the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
61
1
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 29 publications
5
61
1
1
Order By: Relevance
“…2B). Consistent with this finding, mutation in the Arg residue of E͞DRY motif in the N-formyl peptide receptor has also been shown to abolish G protein coupling (19 1A receptors, we used confocal microscopy to monitor translocation of ␤-arrestin 2-GFP to receptors on agonist treatment. When ␤-arrestin 2-GFP was coexpressed with the wildtype AT 1A receptor or the DRY͞AAY mutant receptor, ␤-arrestin 2-GFP was distributed uniformly in the cytoplasm of cells (Fig.…”
Section: Resultsmentioning
confidence: 54%
“…2B). Consistent with this finding, mutation in the Arg residue of E͞DRY motif in the N-formyl peptide receptor has also been shown to abolish G protein coupling (19 1A receptors, we used confocal microscopy to monitor translocation of ␤-arrestin 2-GFP to receptors on agonist treatment. When ␤-arrestin 2-GFP was coexpressed with the wildtype AT 1A receptor or the DRY͞AAY mutant receptor, ␤-arrestin 2-GFP was distributed uniformly in the cytoplasm of cells (Fig.…”
Section: Resultsmentioning
confidence: 54%
“…1). The receptor contains a short N terminus, seven distinct hydrophobic membrane-spanning domains, and the highly conserved DRY motif located at the interface between the third transmembrane helix and the cytoplasm (20). The receptor has only one initiator methionine in the open reading frame, which contrasts with three such putative initiator methionines in MCH 1 .…”
Section: Resultsmentioning
confidence: 93%
“…This suggested that our methods would be amenable to a receptor-arrestin study. The FPR colocalizes with arrestin-2 and arrestin-3 in U937 cells transfected to express the FPR and in neutrophils (30). 2 The addition of wild-type arrestin-3 had no effect on the ligand dissociation rate or sensitivity to guanine nucleotide (Fig.…”
Section: Resultsmentioning
confidence: 99%